Designing Public Open Spaces as a Form of Environmental Identity - Eva Elviana; Sri Suryani; Wiwik Dwi Susanti (Nusantara Science and Technology Proceedings)
The presence of open space in the middle of the buildings can be a counterweight to the environment. Physically the composition between buildings and open space (solid – void) forms a harmony in a spatial pattern. Open space in a residential environment provides a very important function, because the presence of open space can support community activities, such as gathering, and socialization among citizens, playing, cycling and exercising, as well as providing recreational area for residents. On a wider scale, such as urban environment, the presence of public open space can also function as the place of meetings among citizens of different types of men and women, young and old as well as various social status, buying and selling activities, playing ground and recreation, especially in the afternoon or holiday time, as well as other public activities. This shows the importance of the role and function of open space in supporting the activities of citizens and the surrounding environment. This research was conducted to study an open space design with roles and function that can be accommodated there so it can form the character/identity of the environment. The research was done by observing the open space in a simple housing environment and conducting interviews with residents. Further exploring in a design. Characteristic functions and typical community activities in a simple housing environment becomes the dominant factors in forming the traits and identities.